PERANCANGAN MEDIA PEMBELAJARAN LAGU DAERAH DENGAN ANIMASI INTERAKTIF MENGGUNAKAN ADOBE FLASH - Andy Dharmalau; Lela Nurlaela (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
The Indonesia has cultural diversity according to existing regions, one of which is folk songs. It takes the participation of teachers in schools for the introduction and learning of culture in order to remain sustainable. SD Negeri Pejagalan 05 Elementary School Jakarta, has not yet developed computerized learning media for cultural subjects, especially folk songs. Teaching about culture, especially folk songs in schools only focuses on theoretical giving. At the time when learning arts and culture experienced quite a lot of difficulties considering the diversity of regional cultures in the archipelago. The use of learning media as a learning aid is very much needed, while the tools for introducing culture are also very minimal. Based on observations, interviews and analysis of this study using the PIECES theory. Researchers develop learning media in the form of animation, using Adobe Flash CS6 software. In this animation, the material in the form of text and audio is accompanied by an image in the form of a map of Indonesia. The result of this research is the creation of an interactive application of learning folk songs with the Adobe Flash Professional CS6 program. The implementation of the application is made according to expectations.